Guided Inquiry and It's Influence on Evolution Concept Mastery: A Challenge in Islamic Boarding Schools - Ulfa, Winda Maria; Antika, Linda Tri; Haikal, Moch.; Fathir, Akhmad (Universitas Tidar, 2024)
Today's education requires students to manage their learning independently, so that students can set learning goals, set strategies, and even evaluate learning, so that students' understanding of concepts increases. This is related to the learning model used, one of which is guided inquiry. This study aims to determine the influence of guided inquiry on the understanding of the concept of evolution. This study is a quantitative research with a quasi-experimental research design with a non-equivalent pretes-postes control group design The subjects in this study are students of class XII IPA MA Miftahul Ulum Bettet Pamekasan even semester of the 2024/2025 academic year. Class XII Science B is an experimental class with 32 students, while class XII Science C is a control class with 31 students. Sampling was carried out by random sampling technique. The hypothesis test in this study uses the Unpaired T Test. The results showed that there was no influence of guided inquiry on the understanding of the concept of evolution. However, guided inquiry remains a reference for a learning model that can empower a variety of skills for students. Researchers should then consider the factors of student readiness, especially in student habits and learning styles, time factors, and teachers or researchers should have mastered the learning model to be used.